The Late Archaic, Final Archaic and Early Formative Periods in the Casma Valley: Data and Hypotheses - Bischof, Henning (Pontificia Universidad Católica del Perú, 2012)
This paper endeavors to establish some basic points of reference to better understand the early culture-historical dynamics of the Casma Valley. The revised chronology presented here follows the ceramic sequence developed by Peter Fuchs (1990) on the basis of his Cerro Sechín stratigraphy, confirmed and amplified in its early sections by his recent excavations at Sechín Bajo. A systematic review of the different categories of archaeological data reveals many lacunae that still persist in our record. Monumental architecture most clearly expresses the socio-cultural complexity of the ancient Casma Valley polities. It first appeared during the Sechín Period (3400-1650 cal BC) which is part of the Late Archaic (Preceramic), followed during the Early Formative by the Moxeke Period (1650-1400 cal BC) and the Haldas Period (1400-1000 cal BC) with their diagnostic ceramics. Within this timeframe, some hypotheses formulated by Shelia and Thomas Pozorski (2006) about the socio-political transactions between major Casma Valley sites are evaluated in the light of the archaeological evidence. The tradition of monumental adobe architecture that goes back to about 3400 cal BC in the Casma Valley, reminds us of analogous developments in the Pre-Pottery Neolithic of the ancient Near East. There still remains the challenge to adapt Archaic Period terminology in the Andes to those new discoveries (Kaulicke 1994, 2007: 17-18).